Delivery capabilities impact project performance - Roziela, Hassan (2015)
The aim of this research is to study project delivery capabilities impact project performance. If the companies know the factors that influencing the project’s performance, they will focus on that and can deliver the project successfully. For the factors of project delivery capabilities is a set as independent variable. The factors that have been use in this research are process, organizations, methods, metric and leaderships because these are the top five factors that have impact on project performance. Then, the dependent variable of project performance is time. Sixty respondents from the construction industry in Kuantan, Pahang that are registered under CIDB were surveyed by questionnaire. The questionnaires were distributed using mail, google doc, and face to face. Software SPSS was use to analyse the data to get the results. The objectives of this research are to investigate project delivery capabilities practices in project management and to rank the project delivery capabilities according to priorities in project performance Results show that project delivery capabilities impact project performance and the finding are parallel accordance with previous researches but had different ranking of factors.